Perceptions of indigenous ugandan men on the use of long acting reversible contraceptives (LARCs) by rural women - Ronald Arineitwe Kibonire; David D. Mphuthi (BMC, 2023)
Abstract Worldwide, unintended pregnancies remain a critical public health challenge, with 74 million women in low- and middle-income countries getting these pregnancies yearly. The African continent alone contributes about 25% of all unintended pregnancies globally. Even though not all unintended pregnancies are unwanted, they can lead to many health problems for mothers and children, like malnutrition, sickness, neglect, or abuse, as well as maternal and infant morbidities and mortalities. Globally, many women die due to complications related to childbirth, either during or after pregnancy. Contraceptives, especially for long-acting reversible Contraceptive methods (LARCs), are among the best interventions to reduce maternal death. LARCs help the mother delay pregnancy and allow for longer intervals in childbirth spacing. However, utilising LARCs globally and in Uganda remains low because of limited male partner support. The purpose of this phenomenological qualitative research study was to elicit an understanding of the perceptions and beliefs of rural indigenous Ugandan men towards the use of LARCs by rural women. Ultimately the study designed strategies to enhance the uptake of those methods. Purposive sampling was used to identify 65 participants for focus group interviews and 30 for individual interviews comprising married men aged 20 to 49 years. The study was conducted in the Rubanda and Kiboga Districts of Uganda. The researcher used semi-structured questions for individual and focus group interviews. The data analysis was done by transcribing the interviews, sorting the field notes, organising, and storing the data, listening to recordings, and reading field notes and interviews to look for patterns related to the perceptions and belief systems. Using the identified patterns, the researcher coded and categorised the data to build themes emerging on the phenomenon. The study established negative perceptions and belief systems among rural indigenous Ugandan men regarding the use of LARCs by their rural women, which acted as barriers to utilisation. These perceptions included side effects, fears, desires, and cultural and religious beliefs. The study recommends strengthening social and behavioural change communication, strengthening service provision for LARCs, and monitoring and evaluation systems for LARCs. Additionally, policymakers should provide a conducive environment for LARC services provision, and the Ministry of Education and Sports, through health training institutions and universities, should prepare pre-service and in-service healthcare workers to provide LARC services.